2013
DOI: 10.2105/ajph.2013.301367
|View full text |Cite
|
Sign up to set email alerts
|

To Promote Adoption of Household Health Technologies, Think Beyond Health

Abstract: Health risks from poor malaria control, unsafe water, and indoor air pollution are responsible for an important share of the global disease burden-and they can be addressed by efficacious household health technologies that have existed for decades. However, coverage rates of these products among populations at risk remain disappointingly low. We conducted a review of the medical and public health literatures and found that health considerations alone are rarely sufficient motivation for households to adopt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…First Energy found that measuring the lung function of prospective customers to demonstrate the damage from traditional biomass cooking did not appear to boost stove sales; those shown to have poor lung function requested suitable medicines instead (Adler, 2010). This finding is consistent with studies that have cast doubt on the effectiveness of health education as a spur to adoption of health-improving products in the household (Dupas, 2011; Kremer and Miguel, 2007; Luo et al, 2011; Thurber et al, 2013). …”
Section: Resultssupporting
confidence: 90%
“…First Energy found that measuring the lung function of prospective customers to demonstrate the damage from traditional biomass cooking did not appear to boost stove sales; those shown to have poor lung function requested suitable medicines instead (Adler, 2010). This finding is consistent with studies that have cast doubt on the effectiveness of health education as a spur to adoption of health-improving products in the household (Dupas, 2011; Kremer and Miguel, 2007; Luo et al, 2011; Thurber et al, 2013). …”
Section: Resultssupporting
confidence: 90%
“…Instead, studies are recognizing the importance of non-health motives, including cost and intra-household gender dynamics, in adoption decisions 14 , 15 . But even here, the experience can be mixed.…”
Section: Building Demand For Icsmentioning
confidence: 99%
“…But technologies need to be developed using systematic, iterative methods that ensure that they are based on the actual needs of the users and that they will be accessible and scalable. 54 Furthermore, equal priority needs to be placed on both prototype development and a strategy for commercial viability.…”
Section: Discussionmentioning
confidence: 99%